Why do firms collaborate with local universities?. Issue 11 (2nd November 2018) - Fitjar, Rune Dahl; Gjelsvik, Martin
ABSTRACT: This paper examines why firms sometimes collaborate locally rather than with higher-quality universities at a distance. Existing research has mostly relied on the localized knowledge spillover (LKS) model to explain this. This model holds that knowledge transfer across distance is costly, and collaborating locally reduces the risk of information loss when the knowledge is transferred. However, there are various other reasons that could also explain the pattern. If the local university can make a useful contribution, firms might choose to look no further. Firms may also see collaboration as a long-term investment, helping to build research quality at the local university with the hope of benefiting in future. Finally, firms may want to contribute to the local community. We extend the LKS model with these additional motivations and explore their validity using data from 23 semi-structured interviews of firms that collaborate intensively with lower-tier local universities.